Pengaruh Pembayaran Digital, Kejelasan Sasaran Anggaran, dan Sistem Pelaporan terhadap Kinerja BUMDes - M. Rizky Rico Saputra (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to examine the impact of digital payments, budget target clarity, and reporting systems on the performance of Village-Owned Enterprises (BUMDes) in South Lampung Regency. The research background is motivated by the fact that the performance of BUMDes nationally, including in the region, remains relatively low, with most still categorized as pioneers or beginners. The research method used is quantitative with a survey approach using a questionnaire, distributed to 77 BUMDes managers who met the sample criteria. Data were analyzed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) with the SmartPLS 4.0 software. The findings indicate that the reporting system has a significant positive effect on BUMDes' performance. Conversely, digital payments and budget target clarity were found to have no significant effect. These findings imply the importance of strengthening reporting systems that prioritize transparency, accuracy, and ease of access as a strategic step to improve BUMDes performance. Meanwhile, the adoption of digital payments and improved budget planning still require support through enhanced human resource capacity and adequate infrastructure. Practically, this research contributes valuable insights for BUMDes managers and local governments in formulating policies for institutional strengthening.